Perancangan Sistem Reservasi Berbasis Web untuk Pendaftaran Anak pada Jackids Daycare Menggunakan Metode Rapid Application Development (RAD) - Aulia Eka Ayu Putri; Dica Cahyani Putri; Muhammad Rifky Ardi Saputra; Maulana Ardhiansyah (CV. Shofanah Media Berkah, 2026)
This study aims to design and develop a web-based reservation system for child registration at Jackids Daycare using the Rapid Application Development (RAD) method. The system was built using HTML, CSS, JavaScript, and Supabase database. It provides package selection features (Visit, Trial, Daily, Monthly), online registration forms, admin dashboard, and automatic email confirmation. Blackbox testing on 11 pages with 15 scenarios showed all features functioned as expected and were declared valid. The system successfully overcomes manual recording problems at Jackids Daycare by centralizing data, reducing the risk of losing physical forms, and simplifying data search.